Dispersal events of Triassic-Jurassic boundary faunas, and palaeoenvironment of Tibetan Himalaya - Yin, Jiarun; Fürsich, Franz (Science in China Series D-Earth Sciences, 2009)
End-Triassic ammonoid and bivalve faunas of the Germig area, Tibetan Himalaya, lived in a tropical, shallow-water environment during the Triassic-Jurassic boundary interval. High stratigraphic resolution based on ammonite-biochrons allows to tracing the place of origin of several faunal elements. The bivalves Aguilerella and Ctenostreon occurred first in the Tibetan Himalaya and migrated from there to the eastern South Pacific, exhibiting a pantropic dispersal pattern. This dispersal route is supported by the distribution pattern of the ammonites Choristoceras, Discamphiceras, Pleuroacanthites, and Psiloceras calliphyllum. A few taxa, which went extinct everywhere else by the end of the Triassic, survived in the Tibetan Himalaya into early Early Jurassic times. They include the ammonites Choristoceras and Eopsiloceras, and the bivalves Newaagia, Terquemia, Persia, Ryderia guangdongensis, and Cultriopsis angusta. This suggests that the Tibetan Himalaya may have played a refugia role in the course of the end-Triassic mass extinction.
UnivIS-Import:2017-12-18:Pub.2009.nat.dgeo.IGM.LP.disper
Keywords: end-Triassic mass extinction; paleobiogeography; bivalves; ammonites